(untitled) (The Peerian Journal, 2022)
Every culture strives to comprehend its past. National spirituality is built on historical awareness and historical memory. Our country is solidifying its place and position in the world as it comes to terms with its identity through historical consciousness and historical memory. By highlighting their essential connections to consciousness, social awareness, and their position within the framework of national consciousness, this essay demonstrates the substance of the ideas of historical consciousness and historical memory. At the same time, the dynamics and stages of young people’s development of historical consciousness and memory are examined.